Snapin promotes HIV‐1 transmission from dendritic cells by dampening TLR8 signaling - Khatamzas, E; Hipp, M; Gaughan, D; Pichulik, T; Leslie, A; Fernandes, R; Muraro, D; Booth, S; Zausmer, K; Sun, M; Kessler, B; Rowland-Jones, S; et al. (EMBO Press, 2017)
HIV-1 traffics through dendritic cells (DCs) en route to establishing a productive infection in T lymphocytes but fails to induce an innate immune response. Within DC endosomes, HIV-1 somehow evades detection by the pattern-recognition receptor (PRR) toll-like receptor 8 (TLR8). Using a phosphoproteomics approach we identified a robust and diverse signaling cascade triggered by HIV-1 upon entry into human DCs. A secondary siRNA screen of the identified signaling factors revealed several new mediators of HIV-1 trans-infection of CD4+ T cells in DCs, including the dynein motor protein Snapin. Inhibition of Snapin enhanced localization of HIV-1 with TLR8+ early endosomes, triggered a pro-inflammatory response, and inhibited trans-infection of CD4+ T cells. Snapin inhibited TLR8 signaling in the absence of HIV-1, and is a general regulator of endosomal maturation. Thus, we identify a new mechanism of innate immune sensing by TLR8 in DCs, which is exploited by HIV-1 to promote transmission.